2013
DOI: 10.1177/1550059413489975
|View full text |Cite
|
Sign up to set email alerts
|

Orthographic Recognition in Late Adolescents

Abstract: Reading speed and efficiency are achieved through the automatic recognition of written words. Difficulties in learning and recognizing the orthography of words can arise despite reiterative exposure to texts. This study aimed to investigate, in native Spanish-speaking late adolescents, how different levels of orthographic knowledge might result in behavioral and event-related brain potential differences during the recognition of orthographic errors. Forty-five healthy high school students were selected and div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 44 publications
3
10
0
4
Order By: Relevance
“…Our results are also compatible with those of González-Garrido, Gómez-Velázquez, and Rodríguez-Santillán, (2014), who suggest that the electrophysiological correlates of orthographic errors processing have shown that adults with low orthographic abilities have problems in detecting orthographic rule violations, which could indicate weak representations in the orthographic lexicon or a difficulty in automatically accessing such representations.…”
Section: Discussionsupporting
confidence: 92%
“…Our results are also compatible with those of González-Garrido, Gómez-Velázquez, and Rodríguez-Santillán, (2014), who suggest that the electrophysiological correlates of orthographic errors processing have shown that adults with low orthographic abilities have problems in detecting orthographic rule violations, which could indicate weak representations in the orthographic lexicon or a difficulty in automatically accessing such representations.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, it has been shown that children with reading difficulties have concurrent spelling problems [27] [28], and that adolescents with low orthographic knowledge show slow reading and difficulty in recognizing phonological spelling errors in Spanish [29].…”
Section: Introductionmentioning
confidence: 99%
“…Se ha reportado, por ejemplo, que una mayor proporción de jóvenes con pobre conocimiento ortográfico y bajo rendimiento lector no continúan estudiando después del bachillerato, en comparación con aquéllos jóvenes con un conocimiento ortográfico y una lectura normales (González-Garrido, et al, 2014). La mayoría de ellos no tienen un diagnóstico de dificultades lectoras, debido principalmente a la falta de consenso en el ambito académico sobre los rasgos distintivos de la dislexia en el adulto y a la falta de instrumentos diagnósticos fiables y de aplicación rápida, que permitan detectar tempranamente el problema.…”
Section: Introductionunclassified